Regulatory Measures Expedited Hip Fracture Surgery Without Lowering Overall Patient Mortality. Issue 4 (24th December 2018) - Schermann, Haggai; Gurel, Ron; Rotman, Dani; Chechik, Ofir; Sternheim, Amir; Salai, Moshe; Ben‐Tov, Tomer; Kadar, Assaf
Abstract : OBJECTIVES: Previous observational research has shown that elderly patients with hip fractures who are operated early (within 48 hours from admission) benefit from less short‐ and long‐term mortality compared to those operated later. The objective of this study was to present regulatory measures aimed at promotion of early hip fracture surgery and their effect on the rates of early surgery and on postoperative mortality. DESIGN: Retrospective cohort. SETTING: Single inner‐city medical center. PARTICIPANTS: Elderly patients with hip fractures operated during three time periods: 2006 to 2009 (n = 1735, no intervention), 2010 to 2013 (n = 2104, first intervention, positive reinforcement), and 2014 to 2016 (n = 1538, second intervention, positive and negative reinforcement). INTERVENTION: Two regulatory measures were introduced consecutively: staff extra wages for afternoon operations (positive reinforcement) in 2010 and making early operation rates publicly available as the Ministry of Health Quality Care Indexes (negative reinforcement) in 2013. MEASUREMENTS: Percentage of early surgeries and mortality at 1 month and 1 year postoperatively. RESULTS: A total of 5377 patients (1595 men, 3782 women; mean age, 83.1 ± 7.2 years) underwent hip surgery between 2006 and 2016. The three study groups did not differ significantly in age on admission, sex, type of hip fracture (intracapsular or extracapsular), American Society of Anesthesiologists' score, mean hemoglobin on admission, and mean socioeconomic status. The percentage of operations performed within 48 hours was 55%, 65%, and 85%, respectively ( P < .001). One‐month mortality was 3.9%, 5.1%, and 5%, respectively ( P > .05), and one‐year mortality was 19.2%, 18.7%, and 19.6%, respectively ( P > .05). CONCLUSIONS: Management pressure on the staff to expedite hip surgery and avoid negative publicity in conjunction with additional wages for afternoon surgeries was successful at promoting earlier hip surgery. Despite the substantial increase in the rates of early surgery, however, mortality rates were not affected. J Am Geriatr Soc 67:777–783, 2019.